One year bacteriological survey of the Iloilo River an assessment of the river sanitary quality - Sinoben, Roche P. ([Miag-ao, Iloilo] University of the Philippines Visayas, 2010)
Three sampling areas, the Forbes Bridge, IBRD Bridge and Carpenters Bridge, were chosen according to contamination exposure and economic significance. Monthly sampling was done on water and bottom sediment to determine the heterotrophic plate count (HPC), total coliform count (TCC), fecal coliform count (FCC) and fecal streptococci count (FSC). The presence of Escherichia coli, Salmonella spp., Vibrio spp. and fecal streptococci spp. were also examined. Specifically, the degree of contamination was determined using HPC and FCC as criteria. Monitoring of some physic-chemical parameters in all sampling areas revealed that pH (6.5 - 8.5), temperature (3 max risetemperature, and salinity were within the range set by Department of Environment and Natural Resources-Environmental Monitoring Bureau for Class C water body except fortemperature, and salinity were within the range set by Department of Environment and Natural Resources-Environmental Monitoring Bureau for Class C water body except forthe mean dissolved oxygen (DO) which was lower than standard of 5 mg/L. High pH level (7.62) significantly raised and lowered TCC and FCC respectively in the water and bottomsediments. Increase in water temperature (29.590C) lowered water FSC and bottom sediments FCC and FSC while high do level (3.71 mg/L) respectively raised and lowered and TCC in water and bottom sediments. Bacterial counts showed a yearly seasonal variation. For both water and sediment samples, consistent low HPC (104.27 -105.70 CFU/100ml water or gsediment), FCC (103.46 -102.20 MPN/100ml water or g sediment), and FSC (102.63- 103.89) MPN/100ml water or g sediment) were noted during the wet season, suggesting that increased waterinflow might have washed off the bacteria thriving in the sampling areas as opposed to the common knowledge that storm water runoff brings more microorganisms to the river that receives them. On the contrary high HPC (104.87- 106.49 CFU/100ml water or g sediment), FCC (103.46 -102.20 MPN/100ml water or g sediment), MPN/100ml water or g sediment), and FSC (102.63- 103.89) were noted during the wet season, i..e. between the months of June and Septembersuggesting that increased water inflow might have washed off the bacteria thriving in the sampling areas as opposed to the common knowledge that storm water runoff brings more microorganisms to the river that receives them. On the contrary high HPC (104.87- 106.49 CFU/100ml water or g sediment), FCC 103.06 - 104.38 MPN/100ml water or g sediment), TCC (103.07 - 104.38 CFU/100ml water or g sediment) and FSC (103.06 - 104.38 MPN/100ml water or g sediment), TCC (103.07 - 104.38 CFU/100ml water or g sediment) and FSC (102.52 - 104.38 CFU/100ml water or g sediment) were observed during the dry season. Potential pathogenic bcteria of human and animal origin such as Vibrio spp. Streptococcus spp., Salmonella spp. and E. coli were detected in the water and bottom sediment samples obtained from all sampling areasAssessment of the surface water revealed moderately high fecal contaminant while the bottom sediments have very little to moderate .load of easily decomposing organic matter and fecal contaminant. Taken together, the current data indicate that the sanitary quality of the Iloilo River is very low based on the standard (5,000 MPN/100ml) for Class C water and the United States Bathing Water Quality Standards (2,4000 MPN/100ml)
Thesis (M. S. Biology) -- [Miagao, Iloilo[ : U. P. Visayas, April 2010.